Prevalence of and factors influencing postnatal depression in a rural community in South Africa - Ethelwynn L. Stellenberg; Johanna M. Abrahams (AOSIS, 2015)
Background: Knowledge about postnatal depression (PND) and associated risk factors whichin fluence the development of PND is vital for early detection, intervention and prevention. Setting: The study was conducted in primary health care clinics (PHC) in the Witzenberg subdistrict, a rural community in South Africa.Objectives: Objectives of this study were to determine the prevalence of PND and to identify the contributing risk factors associated with PND. Methods: A descriptive cross sectional research design with a quantitative approach was applied. The target population was mothers, 18 years and older. A convenience sampling method was used to select a sample of 159 (10%) from a population of 1605 live births. Th eEdinburgh Postnatal Depression Scale (EPDS) and Beck Depression Inventory (BDI), two validated self-rating questionnaires, including a questionnaire based on demographical, psychosocial and obstetrical data, were applied. The data was analysed using various statistical tests to determine statistical associations between variables using a 95% confidence interval. Results: PND was a serious health problem with 50.3% of the mothers who suffered from PND. A BDI analysis showed that of the participants who had PND, 28.8% was severe, 48.8% moderate and 22.5% mild. Factors influencing the development of PND included most participants (63.5%) were unmarried, 61.3% were unemployed and the majority (53.8%) had a history of a psychiatric illness. Significant associations between PND and unplanned and unwelcome babies (p < 0.01); partner relationship (p < 0.01); were identified. Conclusion: Prevention, early detection, appropriate referral and treatment of PND are critical in managing maternal, child and family well-being.